‘Assessing patients’ perception of the potential utility of visual function home monitoring app among patients with diabetes in Saudi Arabia’ - Hanan Khalid Mofty; Marwan A Abouammoh; Hala A Al-Muqbil; Khaled S AL-Zahrani; Talhah M AL-Ghasham; Abdullah A Assiri; Ahmad T AL-Mnaizel; Hayat S Mushcab; Kholoud A Bokhary; Ruth E Hogg (Digital Health)
Aims To determine the acceptability and identify potential concerns and barriers of using a hypothetical smartphone application (app) for home monitoring (HM) of visual function among patients with diabetes. Methods Quantitative, cross-sectional study using a self-administered questionnaire. Patients diagnosed with diabetes aged between 20 and 70 years were included. The research was conducted across five regions in Saudi Arabia. The questions were adapted from a validated, published questionnaire and translated into Arabic. It focused on socio-demographic factors and barriers which associated with the acceptance of the hypothetical visual function HM app, using descriptive statistics. Results A total of 240 patients with diabetes participated in this study. About half of the participants (40.4%) ranged between 40 and 59 years; 42.5% were male, and most of the participants (93.8%) lived within 2 h of their healthcare facility. The rejection to the use of a hypothetical HM app was associated with increased age ( p  = 0.025), lower education level ( p  = 0.023), urbanicity ( p  = 0.011), residing closer to health centres ( p  = 0.021), and never experiencing telehealth services previously ( p  = 0.025). Logistic regression revealed that accepting a hybrid clinic approach was more likely to be acceptable by younger patients (20–39 years: OR, 5.01; 95% CI, 1.82–13.82; p  < 0.001; and 40–59 years: OR, 2.28; 95% CI, 0.084–5.00; p  = 0.48), as well as patients who attended primary healthcare or specialised governmental clinics ( p  = 0.038 and p  = 0.019, respectively). Conclusion Factors that altered patients’ acceptance of the hypothetical app included their age, educational level, urbanicity, traveling distance, and telehealth experience. Therefore, careful consideration of acceptability and barriers is essential before implementing such an intervention.